SYNCHRONIC RECEPTION OF ERNEST HEMINGWAY’S SELECTED SHORT STORIES (A READER RESPONSE APPROACH) - Maria Fradesanti; Fety Surfaifel; Febe F I Wanggai; Marianus W Liru; Maksimilianus Doi (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2026)
This study, titled